Autophagy is inhibited by ubiquitin ligase activity in the nervous system - Crawley, Oliver (Nat Commun, 2019)
Autophagy is an intracellular catabolic process prominent in starvation, aging and disease. Neuronal autophagy is particularly important, as it affects the development and function of the nervous system, and is heavily implicated in neurodegenerative disease. Nonetheless, how autophagy is regulated in neurons remains poorly understood. Using an unbiased proteomics approach, we demonstrate that the primary initiator of autophagy, the UNC-51/ULK kinase, is negatively regulated by the ubiquitin ligase RPM-1. RPM-1 ubiquitin ligase activity restricts UNC-51 and autophagosome formation within specific axonal compartments, and exerts effects broadly across the nervous system. By restraining UNC-51 activity, RPM-1 inhibits autophagosome formation to affect axon termination, synapse maintenance and behavioral habituation. These results demonstrate how UNC-51 and autophagy are regulated subcellularly in axons, and unveils a mechanism for restricting initiation of autophagy across the nervous system. Our findings have important implications beyond nervous system development, given growing links between altered autophagy regulation and neurodegenerative diseases.